Tracing variability of run‐off generation in mountainous permafrost of semi‐arid north‐eastern Mongolia. Issue 6 (18th May 2014) - Lange, Jens; Kopp, Benjamin Johannes; Bents, Matthias; Menzel, Lucas
Abstract The headwaters of mountainous, discontinuous permafrost regions in north‐eastern Mongolia are important water resources for the semi‐arid country, but little is known about hydrological processes there. Run‐off generation on south‐facing slopes, which are devoid of permafrost, has so far been neglected and is totally unknown for areas that have been affected by recent forest fires. To fill this knowledge gap, the present study applied artificial tracers on a steppe‐vegetated south‐facing and on two north‐facing slopes, burned and unburned. Combined sprinkling and dye tracer experiments were used to visualize processes of infiltration and water fluxes in the unsaturated zone. On the unburned north‐facing slope, rapid and widespread infiltration through a wet organic layer was observed down to the permafrost. On the burned profile, rapid infiltration occurred through a combusted organic and underlying mineral layer. Stained water seeped out at the bottom of both profiles suggesting a general tendency to subsurface stormflow (SSF). Ongoing SSF could directly be studied 24 h after a high‐intensity rainfall event on a 55‐m hillslope section in the burned forest. Measurements of water temperature proved the role of the permafrost layer as a base horizon for SSF. Repeated tracer injections allowed direct insights into SSF dynamics: A first injection suggested rather slow dispersive subsurface flow paths; whereas 18 h later, a second injection traced a more preferential flow system with 20 times quicker flow velocities. We speculate that these pronounced SSF dynamics are limited to burned slopes where a thermally insulating organic layer is absent. On three south‐facing soil profiles, the applied tracer remained in the uppermost 5 cm of a silt‐rich mineral soil horizon. No signs of preferential infiltration could be found, which suggested reduced biological activity under a harsh, dry and cold climate. Instead, direct observations, distributed tracers and charcoal samples provided evidence for the occurrence of overland flow. Copyright © 2014 John Wiley & Sons, Ltd.